Analysis Of The Influence Of The Remuneration System On Employee Work Quality - Sihombing, Jonmaianto; Yopi (Journal of Science Education and Management Business, 2025)
This research aims to test and analyze the influence of the remuneration system, work environment and employee characteristics on employee performance through job satisfaction. The population of this study was 80 employees of PT Persero Batam. The sampling technique uses purposive sampling. The number of samples obtained for this research was 68 samples, namely employees of PT Persero Batam with staff positions and who were permanent employees. The data collection technique uses a Google Form questionnaire. This research is quantitative research using the SEM-PLS method through the Smart-PLS 4 application. The results of the research show that (1) the remuneration system has a positive and significant effect on employee performance, (2) the work environment has a positive and insignificant effect on performance, (3) ) Employee characteristics have a positive and significant effect on performance, (4) The remuneration system has a positive and significant effect on job satisfaction, (5) The work environment has a positive and insignificant effect on job satisfaction, (6) Employee characteristics have a positive and significant effect on job satisfaction, (7) Job satisfaction has a positive effect and significant effect on employee performance, (8) The remuneration system has a positive and significant effect on employee performance through job satisfaction, (9) The work environment has a positive and insignificant effect on employee performance through job satisfaction, and (10) Employee characteristics have a positive and significant effect on performance employees through job satisfaction